2015
DOI: 10.1080/09537325.2015.1061121
|View full text |Cite
|
Sign up to set email alerts
|

Customer preferences versus managerial decision-making in open innovation communities: the case of Starbucks

Abstract: Customers can participate in open innovation communities posting innovation ideas, which in turn can receive comments and votes from the rest of the community, highlighting user preferences. However, the final decision about implementing innovations corresponds to the company. This paper is focused on the customers' activity in open innovation communities. The aim is to identify the main topics of customers' interests in order to compare these topics with managerial decision-making. The results obtained reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Several researchers have expressed that, when a company is perceived as innovative, this becomes a part of its image [3,105]. Martínez-Torres et al [169] studied open innovation and customers' activity in innovation communities, taking into account user preferences, comments, and votes. Their research found that managerial decisions are more focused on the features associated with brand image.…”
Section: Innovation and Imagementioning
confidence: 99%
“…Several researchers have expressed that, when a company is perceived as innovative, this becomes a part of its image [3,105]. Martínez-Torres et al [169] studied open innovation and customers' activity in innovation communities, taking into account user preferences, comments, and votes. Their research found that managerial decisions are more focused on the features associated with brand image.…”
Section: Innovation and Imagementioning
confidence: 99%
“…The above analysis reveals a vast amount of research emphasizing the importance of consumer involvement (Kujala, ; Martínez‐Torres, Rodriguez‐Piñero, & Toral, ). The literature mentions many reasons why firms choose to involve consumers in their product development (Laage‐Hellman, Lind, & Perna, ), such as to enhance product performance, reduce development costs, and increase the effectiveness of the product development process (Lin et al., ).…”
mentioning
confidence: 99%
“…Identification of main themes and topics has been extensively conducted in asynchronous online discussions to obtain the preferences of users. For instance, topic modelling was applied to obtain the preferences of Starbucks consumers (Martínez-Torres et al, 2015a) and the main topics of discussion in the open innovation community of Dell, called Dell IdeaStorm (Martínez-Torres, 2015). It has also been used to measure the quality of discourse by identifying the main themes and their magnitude in online discussions (Kovanović et al, 2015).…”
Section: Methodological Approaches To the Analysis Of Discoursementioning
confidence: 99%
“…The collection of data can be automated using a computer programme accessing the source code in HTML. While browsing the website, the computer programme can discriminate the meaningful information and store the relevant variables for the study (Martínez-Torres et al, 2015a).…”
Section: Data Setmentioning
confidence: 99%